Genital Prolapse and Obstetrical Management in Buffaloes- A Retrospective Study - Allada, Udaya Kiran; Banisetty, Sonia; Nuka, Likitha; Paidi, Saranya; Fransis, Sebastin Raju; Kanu gonu, Anthony Raju (The Indian Journal of Animal Reproduction, 2026)
The present study was carried out in buffaloes affected with different grades of genital prolapse (vaginal and uterine pro lapse) during different season and its obstetrical management. The current study included a total of 46 graded Murrah buffaloes diagnosed with genital prolapse, comprising vaginal prolapse (n=24) and uterine prolapse (n=22). The greater incidence of genital prolapse was recorded during the autumn season around 2nd lactation. Among the vaginal prolapse cases, Grade 1 was the most prevalent (41.66%), followed by Grade 4 (25%), Grade 3 (20.8%), and Grade 2 (14.29%). In all cases of Grade 2 and 3 vaginal prolapse as well as in uterine prolapse, manual repositioning of the prolapsed mass and retention with Buhner’s suture technique was found effective.